Pengaruh Penggunaan Media Sosial Youtube terhadap Akhlak Anak Usia Sekolah Dasar di Desa Sidoharjo Kecamatan Jati Agung Kabupaten Lampung Selatan - Risalatus Solihah; Mustaqim Hasan; Ratika Novianti (Journal on Education, 2024)
This research examines the influence of the use of YouTube social media on the morals of elementary school age children. In the current digital era, YouTube has become a very popular platform among children to access various entertainment and educational content. This research aims to obtain evidence of a causal relationship between the independent variable, namely Social Media (X) and the dependent variable, namely the Morals of Elementary School Age Children (Y). The research method used in this research is quantitative. Data collection tools use questionnaires, documentation and observation. The research will be carried out in Sidoharjo Village, Jati Agung District, South Lampung Regency. The population used was 248 people and the sample used was 50 people taken by random sampling. Data analysis uses classic assumption tests, namely normality and homogeneity tests and hyposcription tests use simple regression tests. The research results show that based on the results of linear regression testing the influence of using YouTobe social media on children's morals, it can be concluded that there is an influence. This can be seen based on the SPSS output, it is known that the significance value (Sig.) of 0.012 is smaller than the probability of 0.05, so it can be concluded that Ho is rejected and Ha is accepted, which means that there is an influence of social media use on students' morals. The contribution of social media to the morals of elementary school aged children can be seen from the Model Summary output. It is known that the R Square value is 0.648. This value means that the influence of using YouTube social media on students' morals is 64.8%, while 35.2% of children's morals are influenced by other variables. . Based on these results, it can be concluded that the use of YouTube social media greatly influences students' morals, both good morals and bad morals.